Essays in Intergenerational Mobility and Public Economics - FONSECA, Alexandre de Andrade (2024)
This thesis addresses issues of intergenerational mobility and public economy, studying intergen- erational mobility in Brazil, the effects of conditional cash transfer policies and rural property taxation. In the first chapter, I provide the first estimates of intergenerational income mobility using population wide tax data for a large developing country, namely Brazil. I measure formal income from tax and payroll data, and train machine learning models on census and survey data to predict informal income. I quantify the estimation bias resulting from income imputation and other sources of measurement error, and show that such bias remains negligible in our context. A 10 percentile increase in parental income rank is associated on average with a 5.5 percentile increase in child income rank, with considerable variation across sociodemographic groups and geographical areas. The second essay examines the intergenerational effects of the world’s largest conditional cash transfer (CCT) program, Brazil’s Bolsa Família Program (PBF). Employing a differences-in-differences design and a comprehensive dataset covering cohorts born between 1970–1994. I reveal that PBF significantly promotes human capital accumulation, leading to reduced dependency on the social safety net, higher earnings, and intergenerational income mobility among the next generation. These effects are more pronounced for younger children and females, highlighting the importance of early exposure to the program and its role as a driver of greater equality. My findings underscore the effectiveness of CCTs in breaking the intergenerational cycle of poverty and fostering social mobility. The third chapter uses a difference-in-differences research design to evaluate a program that partially decentralized the administration of rural land taxes to local authorities in exchange of increases in their share of tax revenues. Using microdata from tax returns, I find that the program led to an expansion of tax revenues by 20% after five years. Decentralization expanded tax revenues mainly by increasing reported land values. Using satellite data, I find that partial decentralization did not influence farmer behavior significantly. A cost-benefit exercise indicates that partial decentralization had large returns. Overall, the findings indicate that cooperation between local and central authorities can increase property taxation in contexts with incomplete information and weak enforcement capacity.